Pelatihan Pembelajaran Bahasa Inggris Anak Usia Dini Pada Guru TK Di Kecamatan Rappocini Kota Makassar - A. Sri Wahyuni Asti; Muhammad Akil Musi; Hajerah; Fadhilah Afifah; Amal, Azizah (Ininnawa : Jurnal Pengabdian Masyarakat, 2024)
This training program aims to enhance the competency of kindergarten teachers in teaching English to young learners in Rappocini District, Makassar City. The training combines theoretical and practical approaches, including simulations, workshops, and relevant material development. The focus is on interactive teaching by using songs, stories, games, and crafts to create a fun learning environment for children. Through phases of preparation, theoretical instruction, practice, and evaluation, participants are provided opportunities to refine their teaching skills and confidence in delivering English lessons. Results indicate that teachers improved their creativity and variety in lesson planning, which is expected to positively impact the quality of English education at the early childhood level and establish a replicable training model for other regions.